A Practical Scheduling Method for Multiclass Production Systems with Setups - Olsen, Tava Lennon (Management Science, 1999)
Consider a multiclass production system where many job classes share a single server and a setup time is incurred whenever the server changes class. This paper presents a simple method for scheduling these systems that performs well, not only with respect to mean waiting time, but also with respect to waiting-time variance and the outer percentiles of waiting time. The scheduling method is dynamic and uses the ages of items in each queue, as well as the queue statistics, to decide which queue to service next.